2014
DOI: 10.1111/dme.12392
|View full text |Cite
|
Sign up to set email alerts
|

Associations of blood glucose and prevalent diabetes with risk of cardiovascular disease in 500 000 adult Chinese: the China Kadoorie Biobank

Abstract: AimsTo examine the relationship of self‐reported diabetes, and of random blood glucose levels among individuals without known diabetes, with the prevalence of cardiovascular disease in Chinese adults.MethodsWe examined cross‐sectional data from the China Kadoorie Biobank of 0.5 million people aged 30–79 years recruited from 10 diverse regions of China in the period 2004–2008. Logistic regression was used to estimate the odds ratios of prevalent cardiovascular disease associated with self‐reported diabetes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
2
39
0
2
Order By: Relevance
“…For all vascular outcomes, controls excluded individuals reporting a history of CHD, stroke or transient ischaemic attack at baseline, or incident MVE. Tertiary outcomes were diabetes and COPD, including both prevalent (previous history or screen-detected 22 , 23 ) and incident cases and incident chronic kidney disease, liver disease, inflammatory disease, cancer and non-vascular death. Controls excluded individuals reporting a history of that disease at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…For all vascular outcomes, controls excluded individuals reporting a history of CHD, stroke or transient ischaemic attack at baseline, or incident MVE. Tertiary outcomes were diabetes and COPD, including both prevalent (previous history or screen-detected 22 , 23 ) and incident cases and incident chronic kidney disease, liver disease, inflammatory disease, cancer and non-vascular death. Controls excluded individuals reporting a history of that disease at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Общеизвестно, что сахарный диабет (СД) наравне с такими традиционными факторами риска как арте-риальная гипертония (АГ), курение, ожирение и нарушение липидного обмена является значимым фактором риска развития сердечно-сосудистых забо-леваний (ССЗ) и их осложнений [1][2][3]. При этом, некоторыми исследователями показаны достоверные ассоциации уровня глюкозы с риском развития ССЗ и смертности, независимо от наличия СД [4,5].…”
Section: Association Of Glucose With General and Cardiovascular Mortaunclassified
“…The risk of CVD event is two to three times higher in people with diabetes [3•, 18]. A recent study of 50,000 Chinese adults revealed that diabetes was associated with a doubling of the odds of prevalent cardiovascular disease [20].…”
Section: Diabetesmentioning
confidence: 99%
“…Harmful use of alcohol accounted for an estimated 4.5 % of DALYs globally [20]. High levels of alcohol consumption (>60 g of pure alcohol per day) is reported to be associated …”
Section: Alcoholismmentioning
confidence: 99%
See 1 more Smart Citation